Targeting the tumor stroma with an oncolytic adenovirus secreting a fibroblast activation protein-targeted bispecific T-cell engager. Issue 1 (25th January 2019) - de Sostoa, Jana; Fajardo, Carlos Alberto; Moreno, Rafael; Ramos, Maria D.; Farrera-Sal, Martí; Alemany, Ramon
Abstract : Background: Oncolytic virus (OV)-based therapies have an emerging role in the treatment of solid tumors, involving both direct cell lysis and immunogenic cell death. Nonetheless, tumor-associated stroma limits the efficacy of oncolytic viruses by forming a barrier that blocks efficient viral penetration and spread. The stroma also plays a critical role in progression, immunosuppression and invasiveness of cancer. Fibroblast activation protein-α (FAP) is highly overexpressed in cancer-associated fibroblasts (CAFs), the main cellular component of tumor stroma, and in this study we assessed whether arming oncolytic adenovirus (OAd) with a FAP-targeting Bispecific T-cell Engager (FBiTE) could retarget infiltrated lymphocytes towards CAFs, enhancing viral spread and T cell-mediated cytotoxicity against the tumor stroma to improve therapeutic activity. Methods: The bispecific T-cell Engager against FAP was constructed using an anti-human CD3 single-chain variable fragment (scFv) linked to an anti-murine and human FAP scFv. This FBiTE was inserted in the oncolytic adenovirus ICOVIR15K under the control of the major late promoter, generating the ICO15K-FBiTE. ICO15K-FBiTE replication and potency were assessed in HT1080 and A549 tumor cell lines. The expression of the FBiTE and the activation and proliferation of T cells that induced along with the T cell-mediated cytotoxicity of CAFs were evaluated by flow cytometry in vitro . In vivo, T-cell biodistribution and antitumor efficacy studies were conducted in NOD/ scid / IL2rg − / − (NSG) mice. Results: FBiTE expression did not decrease the infectivity and replication potency of the armed virus . FBiTE-mediated binding of CD3 + effector T cells and FAP + target cells led to T-cell activation, proliferation, and cytotoxicity of FAP-positive cells in vitro . In vivo, FBiTE expression increased intratumoral accumulation of T cells and decreased the level of FAP, a marker of CAFs, in tumors. The antitumor activity of the FBiTE-armed adenovirus was superior to the parental virus. Conclusions: Combination of viral oncolysis of cancer cells and FBiTE-mediated cytotoxicity of FAP-expressing CAFs might be an effective strategy to overcome a key limitation of oncolytic virotherapy, encouraging its further clinical development.